Polyuria and polydipsia revealing a pituitary metastasis: Report of a rare case - Ghassen Gader; Skander Guediche; Mohamed Ben Hadj Yahya; Mohamed Zouaghi; Mouna Rkhami; Mohamed Badri; Ihsèn Zammel (Clinical Case Reports, 2022)
Abstract Sellar region is a rare localization for intracranial metastases. The diagnosis is frequently delayed as symptoms are generally non specific. Radiologic diagnosis may be difficult as these tumours present similiraities to other more frequent sellar tumours. There is still no consensus regarding therapeutic approach. Prognosis is related to several features.